The Role of Class Teachers in Increasing Elementary School Students' PPKn Learning Motivation - Miftahul Jannah; Mila Septian Haryati; Nurwahidah, Nurwahidah (Yayasan Insan Mulia Bima, 2025)
The purpose of this study, namely; 1) to determine the role of teachers in motivating students to learn PPKn; 2) To determine the efforts of teachers to overcome obstacles to PPKn learning motivation. This study is a qualitative descriptive study that aims to describe the role of grade IV teachers of SDN Ragi in increasing their students' PPKn learning motivation. This study involved 38 grade IV students as research subjects. Data collection was carried out through observation, interviews, and documentation involving teachers, students, and school facilities and infrastructure. The results of the study showed that teachers act as motivators by creating an active and enjoyable learning atmosphere, as well as dynamicators by creating a conducive classroom atmosphere. Some of the obstacles faced by teachers include students who tend to play during learning and the lack of student independence in working on questions. To overcome these obstacles, teachers apply various solutions such as ice breaking, advice, praise, punishment, awards, training students to work on questions at school, and giving homework.